Topological transformation of microbial proteins into iron single-atom sites for selective hydrogen peroxide electrosynthesis - Xiaofeng Xiao; Zechao Zhuang; Shuhu Yin; Jiexin Zhu; Tao Gan; Ruohan Yu; Jinsong Wu; Xiaochun Tian; Yanxia Jiang; Dingsheng Wang; Feng Zhao (Nature Communications)
Abstract The emergence of single-atom catalysts offers exciting prospects for the green production of hydrogen peroxide; however, their optimal local structure and the underlying structure–activity relationships remain unclear. Here we show trace Fe, up to 278 mg/kg and derived from microbial protein, serve as precursors to synthesize a variety of Fe single-atom catalysts containing FeN5−x O x (1 ≤ x ≤ 4) moieties through controlled pyrolysis. These moieties resemble the structural features of nonheme Fe-dependent enzymes while being effectively confined on a microbe-derived, electrically conductive carbon support, enabling high-current density electrolysis. A comparative analysis involving catalysts derived from eleven representative microbes reveals that the presence of 0.05 wt% Fe single-atom sites leads to a significant 26% increase in hydrogen peroxide selectivity. Remarkably, the optimal catalyst featuring FeN3O2 sites demonstrates a selectivity of up to 93.7% and generates hydrogen peroxide in a flow cell at an impressive rate of 29.6 mol g−1 h−1 at 200 mA cm−2. This work achieves structural fine-tuning of metal single-atom sites at the trace level and provides topological insights into single-atom catalyst design to achieve cost-efficient hydrogen peroxide production.